HIGHLIGHTS 2015 - YEARLY STATUS REPORT EDEN INITIATIVE - Schubert, Daniel; Zabel, Paul; Bamsey, Matthew; Zeidler, Conrad; Vrakking, Vincent (2016)
- 40 °C, heavy snow storms, high wind speeds (~30m/s), total isolation, and six months of almost complete darkness throughout the day. These are only some of the challenges the EDEN team will face during its EDEN ISS space analogue mission, which will start at the end of 2017 at the German Neumayer Station III in Antarctica. It is this human mission that drove and motivated the EDEN team during 2015, the first year of this EU-funded project. With a kick-off meeting in March and a detailed two week design study in September, the EDEN team was heavily involved in design tasks for the Antarctic Mobile Test Facility. With this project, the team is on the forefront of pushing the development boundaries of plant cultivation in space. In early 2015, the EDEN Laboratory was extended by an additional room. This new work area offers space for multi-purpose work tables, additional storage area, a 3D-printer station for advanced prototyping, and a small electronic work station. 2015 was also a year for terrestrial applications. In close collaboration with the Association for Vertical Farming (AFV) and leading scientists from the horticulture sector, the EDEN team conducted its second Vertical Farming study, performed in the Concurrent Engineering Facility (CEF). This advanced farm represents a benchmark design for the future discussion on the applicability of inner city agriculture solutions. In 2015, the ‘EDEN for Kids’ learning- and outreach program was created in close collaboration with the DLR School_lab. With this comprehensive teaching program, the foundation was created to facilitate the challenges of space exploration and sustainable living on Earth. Furthermore in February 2015, Vincent Vrakking joined the EDEN group as a new team member. Vincent, who already conducted his master’s thesis at DLR Bremen on inflatable greenhouse systems, complements the team with his essential knowledge of computer aided design and systems engineering. In September 2015, Chen Dong, a Chinese guest scientist, who lived 105 days in ...